Change and Continuity in Precariousness: Labour Market Policy, Gendered Pathways and COVID-19 Crisis - Bădoi, Delia (Calitatea Vieții, 2021)
The paper employs a theoretically grounded analysis on precarious employment interrelated with gender-based inequalities and labour market changes in the recent COVID-19 outbreak. The concept of precariousness involves a complex understanding of the insecurity of continuous employment on both institutional and individual level. While the post-Fordist society marked radical changes in the labour market, recent neoliberal policies created new vulnerable groups that experience insecurity, the blocking of professional opportunities and insufficient income over time. This article builds on the idea that the 'stable' and 'flexible' labour market normalized the work insecurity in the context of the economic crises and led to precariousness. Work-related insecurity occurs in a gender-segregated labour market. For the exploration of ongoing processes of the precarization phenomenon, this article focuses on the connection between multidimensional concepts covering the economic, social and psychological consequences of labour insecurity. First, the paper aims to discuss a theory-based conceptualisation of precariousness understood as a multidimensional phenomenon in research literature. Second, the paper includes secondary empirical data on precarious employment, absence from work and COVID impact on gender-segregated labour market at the EU level from Eurostat (2020), EIGE (2020), ILO (2020) and Eurofound (2021). Finally, the results problematises existing approaches on precarious employment and gender inequalities in the context of labour market changes of the COVID-19 crisis.